2020
DOI: 10.1002/cite.202000098
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chimney‐draught Conditions on Combustion and Emission Behavior of a Wood‐burning Stove

Abstract: Pollutants from combustion in wood‐burning stoves are influenced by many factors, including the exhaust gas system. This is responsible for the air supply due to the draught generated. Contrary to results reported in literature the experiments in this study show no effect on temperature related to increasing air supply and a total dust decreasing at higher draughts. The results also show no significant impact of the draught on gaseous emissions (CO/OGC/NOx). The most significant loss was determined at thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…A sample is dried at 105 ± 2 °C until its mass remains constant. Due to the standardisation and, thus reproducibility, this method is often used as a reference method for investigations of the accuracy of other or new analysis methods [44][45][46][47][48][49][50][51][52]. Besides the standardised method at 105 °C, the drying process can also be carried out at lower (e.g., 80 °C) or higher (e.g., 130 °C) temperatures.…”
Section: Wet Chemical Methodsmentioning
confidence: 99%
“…A sample is dried at 105 ± 2 °C until its mass remains constant. Due to the standardisation and, thus reproducibility, this method is often used as a reference method for investigations of the accuracy of other or new analysis methods [44][45][46][47][48][49][50][51][52]. Besides the standardised method at 105 °C, the drying process can also be carried out at lower (e.g., 80 °C) or higher (e.g., 130 °C) temperatures.…”
Section: Wet Chemical Methodsmentioning
confidence: 99%
“…In contrast, the ZS (the ZS chimney has a 90°angle at its joints) chimney maintains a higher overall internal stove temperature. Endriss et al 16 showed that the draft influences temperature, while the particulate matter concentrations significantly decreased with the increase in draft. Mehta and Richards 17 experimentally studied a top-lit updraft cook stove and reported that the char remaining at the end of gasification decreased with the increased diameter of the combustion chamber.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the ZS (the ZS chimney has a 90° angle at its joints) chimney maintains a higher overall internal stove temperature. Endriss et al . showed that the draft influences temperature, while the particulate matter concentrations significantly decreased with the increase in draft.…”
Section: Introductionmentioning
confidence: 99%